Evaluation of pre-analytical specimen rejection using Six Sigma metrics: A retrospective single-center study - Xiuli Cheng; Haimiao Yu; Le Zhang; Biao Zhang; Qin Wang (PLoS ONE, 2025)
Background Up to 60% of errors occur in the pre-analytical stage of laboratory testing, potentially impairing clinical decision-making. This study aimed to assess pre-analytical errors using Six Sigma metrics and identify underlying causes for quality improvement. Methods A retrospective analysis of pre-analytical sample errors was conducted over three years in a clinical laboratory. Errors were categorized, and Sigma values were calculated to assess quality. Trends over time were also analyzed. Results Of 2,068,074 samples, 2,214 (0.107%) were rejected. The top errors were clotted blood specimens (67.34%), insufficient volumes (8.22%), and cancelled test requests (6.28%), with Sigma values of 4.42, 5.25, and 5.32, respectively. The outpatient department performed best (Sigma = 5.47), while other wards required improvement. Conclusion Efforts are needed to reduce specimen rejection, particularly clotted samples, to enhance laboratory quality.